1997
DOI: 10.1159/000283055
|View full text |Cite
|
Sign up to set email alerts
|

Leydig Cell Tumor–Comparison of Results of Radical and Testis-Sparing Surgery in a Single Center

Abstract: Between January 1981 and December 1995, 15 patients were treated for Leydig cell tumor at our institution – 12 by radical orchiectomy, 3 by tumor enu-cleation. All patients were contacted to assess the long-term outcome depending on the treatment initially chosen. Follow-up ranged from 8 to 161 months (mean 56). In no case was progressive disease documented, in 1 case local recurrence was witnessed 4 months after tumor enucleation despite negative resection margins. We conclude that a small Leydig cell tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Despite the very small tumours (mean 3.6 mm in diameter) the ratio of benign to malignant lesions in the present series (Table 1) compares well with that of previous studies including larger incidental tumours [15,17]. In a study by Horstman et al [15] including nine impalpable incidental testicular tumours, seven were found to be benign stromal tumours and two were malignant germ cell tumours; in that study the mean tumour diameter was significantly larger, at 8.8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) mm. Another study by Leroy et al [17] included 15 patients, with a mean tumour diameter of 7.5 (4-16) mm; histological analysis showed malignant germ cell tumour in four, while all other lesions were benign.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Despite the very small tumours (mean 3.6 mm in diameter) the ratio of benign to malignant lesions in the present series (Table 1) compares well with that of previous studies including larger incidental tumours [15,17]. In a study by Horstman et al [15] including nine impalpable incidental testicular tumours, seven were found to be benign stromal tumours and two were malignant germ cell tumours; in that study the mean tumour diameter was significantly larger, at 8.8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) mm. Another study by Leroy et al [17] included 15 patients, with a mean tumour diameter of 7.5 (4-16) mm; histological analysis showed malignant germ cell tumour in four, while all other lesions were benign.…”
Section: Discussionsupporting
confidence: 88%
“…US was conducted using a high-frequency linear-array transducer (8)(9)(10)(11)(12)(13) MHz) that allows for high-resolution imaging of the testicles with a maximum lateral spatial resolution of 0.1 mm. Additionally, innovative tools such as TEQ TM ultrasound technology, Native TM tissue harmonic imaging, and compound imaging (Sequoia TM 512US System, Acuson, Siemens, Malvern, PA, USA) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the patient clearly expressed the desire to remain fertile whenever possible. In the literature, testis-sparing surgery is suggested for unifocal and peripheral testicular tumors which are limited to the organ (without infiltration of the rete testis), and which are !3 cm in size [12,17]. Regular clinical and radiological follow-ups are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors favor radical inguinal orchiectomy [20], whereas others suggest testis-sparing surgery [5, 21], especially if there is bilateral occurrence [22]. So far long-term outcomes after selective removal of Leydig cell tumors in children are not well known, although in adults recurrence has been reported [23]. Yuval et al [24]reported a boy with a Leydig cell tumor who remained well 3 years after testis-sparing surgery.…”
Section: Discussionmentioning
confidence: 99%